Empirical research on the relationship between organizational learning capability and success of technological product innovation implementation in electrical and electronics sector - Razli Che Razak; Adam Mat (2011)
The main aim of this paper is to explore the relationship between organizational learning capability and their impact on success of technological product innovation implementation. Research has fairly established that technological innovation is associated with organizational learning. This paper will focuses at implementation phase of innovation process. A total of 115 responses were received from electrical and electronics (E&E) firms in Malaysia. The results of this study showed that there's a significant relationship between participative decision making, experimentation, interaction with external environment and risk taking on success of technological product innovation implementation.